Erosion behavior of materials on basis of tungsten hot pressed in vacuum under mirror Penning discharge plasma impact - Glazunov, G.P.; Baron, D.I.; Bondarenko, M.N.; Konotopskiy, A.L.; Neklyudov, I.M.; Odeychuk, N.P.; Sayenko, S.Yu.; Surkov, A.E.; Tarasov, I.K.; Volkov, E.D. (Вопросы атомной науки и техники, 2007)
The erosion behavior of porous W, W-Ni and W-Cu systems produced by hot pressing in vacuum was examined under exposure to plasmas of mirror Penning discharges in argon, nitrogen, helium and hydrogen. The erosion characteristic behavior in dependence on ion energy and mass is analyzed and discussed. Досліджувалася ерозійна поведінка пористих W, і W-Ni, W-Cu систем, виготовлених гарячим пресуванням у вакуумі при дії стаціонарної плазми відбивних розрядів Пеннінга в аргоні, азоті, гелії і водні. Аналізується і обговорюється поведінка ерозійних характеристик залежно від енергії іонів та їх маси. Исследовалось эрозионное поведение пористых W, и W-Ni, W-Cu систем, изготовленных горячим прессованием в вакууме при воздействии стационарной плазмы отражательных разрядов Пеннинга в аргоне, азоте, гелии и водороде. Анализируется и обсуждается поведение эрозионных характеристик в зависимости от энергии ионов и их массы.